Potential for photogenerated current for silicon based photovoltaic modules in the Atacama Desert. (1st March 2017) - Ferrada, Pablo; Marzo, Aitor; Cabrera, Enrique; Chu, Haifeng; del Campo, Valeria; Rabanal, Jorge; Diaz-Almeida, Daniel; Schneider, Andreas; Kopecek, Radovan
Highlights: PV glass and encapsulants were evaluated in terms of photo-current density ( Jm ). Evaluation was calculated with AM1.17 for Atacama Desert and AM1.5 Reference Spectra. Low UV cutoff EVA led to 2% higher Jm with IBC cell respect to less efficient cells. Comparing spectra, ARC glass & thermoplastic material (TM) led to 25% Jm gain. ARC and TM led to lowest losses due to reflection and absorption (4.8% and 0.9%). Abstract: In order to evaluate module materials, the maximum theoretical value of the photo-generated current density, was calculated. The calculation was performed for four different solar cells, a standard p-type, passivated emitter and rear contact (PERC), bifacial cell and interdigitated back contact (IBC) considering a solar spectrum of Atacama Desert, the transmittance of several glass-encapsulant-glass structures and quantum efficiency. Regarding the solar spectrum in Atacama, an average air mass (AM) at noon for this location averaged 1.17 and the photovoltaic (PV) modules tilt angle was 20°. When studying the impact of using glass and encapsulants combined with a solar cell under the same solar spectrum, ethylene vinyl acetate (EVA) with low ultraviolet (UV) cutoff led to the higher current density values, up to 2% higher with the IBC solar cell compared to the other solar cells. The highest current gain, when studying the impact of the two spectra in the 300–1200 nm wavelength range, was 7.4% for the IBC solar cell, obtained with a standard 3.2 mm glass, a thermoplastic material (TM) as encapsulant. Considering the UV part of the spectrum, the current gain was maximized with a glass with an anti reflection coating (ARC) combined with the TM encapsulant for the IBC solar cell (25%). A quantification of losses due to reflection in the glass and absorption in the encapsulant revealed that the glass with ARC and the TM encapsulant different than EVA led to the lowest reflection and absorption losses. In this case, the reflection and absorption came down to 4.8% and 0.9%, respectively, contrasting with the 7% and 2.8% loss produced with the standard glass and EVA encapsulants.